2011
DOI: 10.3171/2011.6.spine1012
|View full text |Cite
|
Sign up to set email alerts
|

Cervical sagittal plane decompensation after surgery for adolescent idiopathic scoliosis: an effect imparted by postoperative thoracic hypokyphosis

Abstract: The sagittal profile of the thoracic spine is related to that of the cervical spine. The surgical treatment of Lenke Type 1 and 2 curves by using all pedicle screw constructs has a significant hypokyphotic effect on thoracic sagittal plane alignment (19 [86%] of 22 patients). If postoperative thoracic kyphosis is excessively decreased (mean 25.6°, p < 0.05), the cervical spine may decompensate into significant kyphosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 18 publications
2
73
1
3
Order By: Relevance
“…First, more postoperative changes in sagittal alignment were noted for the cervical spine than for the lumbar spine, suggesting that intervertebral disc intensity changes are a mechanical issue caused by corrective fusion surgery and could be easily influenced by sagittal alignment. In fact, Hwang et al [8] reported a correlation between postoperative thoracic kyphosis in AIS patients and cervical alignment and that thoracic hypokyphosis was a risk factor for cervical kyphosis. In addition, several reports have indicated that the three-dimensional correction of thoracic scoliosis in AIS patients had a significant impact on cervical alignment [8][9][10][11][12]21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, more postoperative changes in sagittal alignment were noted for the cervical spine than for the lumbar spine, suggesting that intervertebral disc intensity changes are a mechanical issue caused by corrective fusion surgery and could be easily influenced by sagittal alignment. In fact, Hwang et al [8] reported a correlation between postoperative thoracic kyphosis in AIS patients and cervical alignment and that thoracic hypokyphosis was a risk factor for cervical kyphosis. In addition, several reports have indicated that the three-dimensional correction of thoracic scoliosis in AIS patients had a significant impact on cervical alignment [8][9][10][11][12]21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Hwang et al [8] reported a correlation between postoperative thoracic kyphosis in AIS patients and cervical alignment and that thoracic hypokyphosis was a risk factor for cervical kyphosis. In addition, several reports have indicated that the three-dimensional correction of thoracic scoliosis in AIS patients had a significant impact on cervical alignment [8][9][10][11][12]21,22]. Second, because intervertebral discs of the cervical spine are smaller and narrower than those of the lumbar spine, it may have been difficult to discern signal intensity changes on MRI in a precise manner.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that although information about the relationship between thoracic kyphosis and lumbar lordosis has already been published in the literature, very little has been published about the reaction of the cervical spine to correction of deformity in idiopathic scoliosis. 2 Hilibrand et al 3 were the first to confirm the radiographic relationship between cervical and thoracic alignment in the sagittal plane. They noticed an inverse relationship between thoracic kyphosis and cervical lordosis in idiopathic scoliosis, in other words, the less the thoracic kyphosis the greater the loss of cervical lordosis.…”
Section: Introductionmentioning
confidence: 99%
“…When not corrected, the inversion of the cervical lordosis can cause early degenerative changes, increasing the incidence of cervicalgia. 2,4 Until very recently, the radiographic parameters of the sagittal balance of the cervical spine were typically inferred from a plumb line dropped from the seventh cervical vertebra and were not accurate in measuring the alignment of the cervical spine. 2 There are no standard values for the evaluation parameters of cervical sagittal balance in patients with idiopathic scoliosis defined in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation